Influence of exercise on oxidative stress in patients with heart failure - Sties S.W.* (2018)
© 2018, Springer Science+Business Media, LLC, part of Springer Nature.Reactive oxygen species play an important role in the pathophysiology of heart failure (HF). In contrast, regular physical exercise can promote adaptations to reactive oxygen species that are beneficial for patients with HF. We completed a systematic review of randomized controlled trials that evaluate the influence of exercise on oxidative stress in patients with HF. Articles were searched in the PubMed, Cochrane, SciELO, and LILACS databases. The search was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The quality of the included studies was assessed using the Physiotherapy Evidence Database scale. We selected 12 studies with a total of 353 participants. The included patients had a left ventricle ejection fraction of < 52% and New York Heart Association functional class II or III disease. A significant increase was observed in peak oxygen consumption (between 10 and 46%) in the group that underwent training (TG). There was an improvement in the oxidative capacity of skeletal muscles in the TG, related to the positive activity of mitochondrial cytochrome c oxidase (between 27 and 41%). An increase in the expression of the enzymes glutathione peroxidase (41%), catalase (between 14 and 42%), and superoxide dismutase (74.5%), and a decrease in lipid peroxidation (between 28.8 and 58.5%) were observed in the TG. Physical training positively influenced the cardiorespiratory capacity and enhanced the benefits of oxidant and antioxidant biomarkers in patients with HF. High-intensity training promoted a 15% increase in the plasma total antioxidant capacity, whereas moderate training had no effect.